DESKRIPSI FONETIS BAHASA MELAYU DIALEK SEBERANG KOTA - Eddy Pahar Harahap (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2015)
In the history stated that one of the spread of the Malay language in the province of Jambi. In the subsequent development of Malay language is still used as a style of speech in everyday life Jambi Malay community. Based on observations during this style of speech that is actually still used in accordance with the phonetic is the Malay community Across the city of Jambi. This research data is the phonetic description of Malay dialects across the city of Jambi. In collecting the data, the research instrument is the researcher's own (human instrument). Researchers came to the Malay community residence location for data collection. Phonetic data collection through observation, interviews, and recording. Results of research and discussion, that sounds Malay dialect is phonetically Across town can be classified as follows. Vowel sounds, consisting of; sound [a], a [i], a [i], sound [u], sound [U], sound [e], a [Ɛ], sound [ә], sound [o], and a [O] , Consonant sounds in speech style Malay Dialects Across major cities; sound [b], sound [c], sound [d], sound [g], sound [h [, sound [j], sound [k], a [? 'glottal'], sound [I], a [m], a [n], a [n], sound [ŋ], sound [ń], sound [p], sound [r], sound [R], sound [s], sound [t], sound [w], sound [y]. Malay dialect Across town belonging to the sound of semi vowel / consonant is a sound [w] and sound [y].